Production of bio-indigo from engineered Pseudomonas putida KT2440 harboring tryptophanase and flavin-containing monooxygenase - Kim, Hyun Jin; Kim, Suwon; Lee, Yeda; Shin, Yuni; Choi, Suhye; Oh, Jinok; Jeong, Jaeho; Park, Hyun A.; Ahn, Jungoh; Joo, Jeong Chan; Choi, Kwon Young; Bhatia, Shashi Kant; et al. (Enzyme and Microbial Technology, 2025)
Indigo is a unique blue dye that has been used in the textile industry for centuries and is currently mass-produced commercially through chemical synthesis. However, the use of toxic substrates and reducing agents for chemical synthesis is associated with environmental concerns, necessitating the development of eco-friendly alternatives based on microbial production. In this study, a robust industrial strategy for indigo production was developed using Pseudomonas putida KT2440 as the host strain, which is characterized by its excellent ability to degrade aromatic compounds and high resistance to environmental stress. By introducing the genes tryptophanase (tnaA) and Flavin-containing monooxygenase (FMO), a P. putida HI201 strain was constructed to produce indigo from tryptophan. To enhance the indigo yield, culture conditions, including medium composition, temperature, tryptophan concentration, and shaking speed, were optimized. Under optimal conditions such as TB medium, 15 mM tryptophan, 30°C, 200 rpm, P. putida HI201 biosynthesized 1.31 g/L indigo from tryptophan in a fed-batch fermentation system. The introduction of tnaA and FMO genes also enabled the production of indigo in various P. putida species, and the indigo-producing strain had a blue color, which served as a visual indicator. This study presents a strategy for using P. putida as a host for robust and sustainable microbial production of indigo, highlighting the strain's applicability and efficiency in environment friendly dye synthesis.
Keywords: Blue dyes; Eco-friendly; Environmental concerns; Flavin containing monooxygenase; Indigo; Industrial strategies; Microbial production; Pseudomonas putida; Toxic substrates; Tryptophanase; Bacterial Proteins; Coloring Agents; Fermentation; Indigo Carmine; Industrial Microbiology; Metabolic Engineering; Oxygenases; Pseudomonas putida; Tryptophan; Tryptophanase; Flavin-containing monooxygenase; indigo; Pseudomonas putida; Tryptophanase